2017
DOI: 10.1016/j.sjbs.2017.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic prediction of food effects for Compound A tablet using PBPK model

Abstract: Physiologically based pharmacokinetic (PBPK) modeling has been extensively used to study the factors of effect drug absorption, distribution, metabolize and extraction progress in human. In this study, Compound A(CPD A) is a BCS Class II drug, which has been extensive applied in clinical as lipid-lowering drug, administered orally after food, they displayed positive food effects in human, A PBPK model was built to mechanistic investigate the food effect of CPD A tablet in our study. By using gastroplus™ softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A second area of application in which oral PBPK models can serve as a useful tool is in the investigation of pH and food effects on oral bioavailability [ 44 , 45 , 46 ]. Of the two phenomena, pH effects are much easier to deal with using PBPK models.…”
Section: Applications Of Oral Pbpk Modelsmentioning
confidence: 99%
“…A second area of application in which oral PBPK models can serve as a useful tool is in the investigation of pH and food effects on oral bioavailability [ 44 , 45 , 46 ]. Of the two phenomena, pH effects are much easier to deal with using PBPK models.…”
Section: Applications Of Oral Pbpk Modelsmentioning
confidence: 99%
“…[11][12][13][14][15] Several studies have shown the application of oral PBPK models for assessing food impact. [16][17][18][19][20][21][22][23] In addition, some reports have also pointed out the prospects and challenges related to the use of PBPK for assessing the impact of food. 1,24 However, there still exists a knowledge gap regarding the appropriate development, validation, and use of PBPK modeling approaches for food effect assessment, specifically for regulatory submission purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traditional empirical models, PBPK models are mechanistic in nature, as they integrate physiological processes with drug properties to incorporate biological interactions with drugs, such as dissolution and metabolic enzyme kinetics, and experimental conditions, such as dosing under a fasted or fed state. (Jones et al, 2012;Zhuang and Lu, 2016;Li et al, 2017;Lin and Wong, 2017). In a typical PBPK model, organs are represented as anatomical compartments which are connected by systemic circulation carrying drug.…”
Section: Introductionmentioning
confidence: 99%
“…(Chiang et al, 2013), 2(Davies and Morris, 1993) , 3(Wong et al, 2009), 4(Wong et al, 2010), 5(Kondo et al, 2003), 6 (Ikegami et al, 2003, 7(Kararli, 1995), 8(Willmann et al, 2007), 9(Chen et al, 2008) , 10 (Hall et al, 2012 (Mandikian et al, 2018),12 (Li et al, 2017),13 (Helander and Fändriks, 2014), 14(Jones et al, 2006),15 (Graham et al, 2012),16 (Rabot et al, 1997) This article has not been copyedited and formatted. The final version may differ from this version.…”
mentioning
confidence: 99%